Pengaruh Keterlibatan Pengurus Organisasi Siswa Intra Sekolah (OSIS) terhadap Prestasi Belajar Siswa - Nur Aisyah Agustin Bakhri; Kustati, Martin; Gusmirawati (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
The background to this study is that several activities carried out by the Student Council (OSIS) at SMA Negeri 16 Padang take up some of the students' learning time in class, which could have an impact on the academic performance of students who are members of the Student Council (OSIS). This study aims to determine the extent to which involvement as an administrator of the Intra-School Student Organization (OSIS) affects the academic achievement of students at SMA Negeri 16 Padang. This research method is an Ex Post Facto quantitative study designed with a cross-sectional design, with a population of 48 students who are members of OSIS (the Intra-School Student Organization) at SMA Negeri 16 Padang. The data collection techniques used in this study were observation, questionnaires, and documentation. The results of the study found that involvement as a member of the Intra-School Student Organization (OSIS) had an effect on the academic achievement of students at SMA Negeri 16 Padang, with a percentage of 46.8%. Considering the results of the hypothesis test, we found that H0 was rejected and Ha was accepted, and that there was an influence of involvement as a member of the Intra-School Student Organization (OSIS) on the academic achievement of students at SMA Negeri 16 Padang.